Beberapa Implikasi Teknis Penerapan UU Penataan Ruang - Budhy Tjahjati S Soegijoko (Journal of Regional and City Planning, 1995)
Many problems are still encountered in spatial planning, from planning which is still oriented toward administrative region criteria, the lack legal instruments in spatial control, disparity perception between agencies over the importance of spatial plan pattern as the basis of development, the lack of basis data and accurate information, until the limited ability of spatial planning institutions. Efforts should be done to solve the problems are enhancing the quality and the ability of spatial planning apparatus. In accordance with those efforts, public and business sector participation in spatial planning should be enhanced. Also needed in these efforts is the strengthening of spatial planning control and information system in spatial planning.